Knowledge and Skills Gap of Midwives to Conduct Obstetric Ultrasonography Screening in Primary Health Care Facilities in Kajiado and Kisii Counties, Kenya - Matiang’i, Micah; Ngunju, Priscilla; Nyagero, Josephat; Omogi, Jarim (Scientific Research Publishing, 2020)
Background: Ultrasound remains a tool of much importance in maternity care with midwives regarded as key health professionals when it comes to care of pregnant mothers. There is however limited study on the knowledge and skills gaps of midwives in conducting obstetric ultrasonography screening. The purpose of this study was to assess the specific obstetric ultrasonography knowledge and skills gaps among midwives based in primary health care facilities. Methods: A cross-sectional study employing both qualitative and quantitative method was conducted between July and August 2019 with 274 midwives. A structured questionnaire was used to collect data while Focus group discussion and Key Informants Interview were used to collect qualitative data. Descriptive statistics were used to summarize the data test associations between variables while the qualitative data were used to compliment the questionnaire data in eliciting more information on the gaps. Findings: Almost all (94.5%) the midwives had never been trained on any basic obstetric ultrasound while six of those that had been trained in early stages by the project lacked equipment to practice the acquired skills. More than three quarters of the respondents opined that they wished to provide personalized care services to mothers/clients seeking Antenatal Care Services (ANC) in their community at a fee while only 13.9% had knowledge that obstetric screening should be done before 24 weeks gestation. Four out of ten of the respondents scored themselves a one (1) on the level of confidence they have using an ultrasound machines or technology. Conclusion: There still remains a huge gap as far as training of midwives on basic ultrasound screening is concerned. The lack of basic obstetric ultrasound screening skills is a barrier to rolling out Point of Care Ultrasound (POCUS) screening services. However, midwives are motivated and willing to learn basic ultrasonography skills to further the objectives of Universal Health Coverage (UHC). Concerted efforts should be made to train midwives on basic obstetric ultrasonography skills in addition to availing mobile/hand held ultrasound technology in Primary Health facilities for them to apply the transferred skills. A sustainable business model to enable mothers continuously afford the services is critical as well.
© 2020 by author(s) and Scientific Research Publishing Inc. This work is licensed under the Creative Commons Attribution International License (CC BY 4.0). http://creativecommons.org/licenses/by/4.0/
Keywords: Antenatal Care; Basic Ultrasound Screening; Midwives; Primary Health Care